Answer:
[tex]a_{n}=3+2(n-1)[/tex]
Step-by-step explanation:
Given:
The given sequence is 3, 5, 7, 9
The difference between the second and first term is 5 - 3 = 2
The difference between the third and second term is 7 - 5 = 2
The difference between the fourth and third term is 9 - 7 = 2
So, there is a common difference of 2. Thus a sequence which has the same difference is known as an arithmetic sequence.
The explicit formula to determine the [tex]n^{th}[/tex] term of an arithmetic sequence is given as:
[tex]a_n=a_1+(n-1)d[/tex]
Where, [tex]a_1\rightarrow 1^{st}\ term, d\rightarrow \textrm{common difference}[/tex]
Plug in 3 for [tex]a_1[/tex] and 2 for [tex]d[/tex]. This gives,
[tex]a_{n}=3+(n-1)\times 2[/tex]
Therefore, the explicit formula to represent the given sequence is:
[tex]a_{n}=3+2(n-1)[/tex]